2017
DOI: 10.1155/2017/4328015
|View full text |Cite
|
Sign up to set email alerts
|

Could LC-NE-Dependent Adjustment of Neural Gain Drive Functional Brain Network Reorganization?

Abstract: The locus coeruleus-norepinephrine (LC-NE) system is thought to act at synaptic, cellular, microcircuit, and network levels to facilitate cognitive functions through at least two different processes, not mutually exclusive. Accordingly, as a reset signal, the LC-NE system could trigger brain network reorganizations in response to salient information in the environment and/or adjust the neural gain within its target regions to optimize behavioral responses. Here, we provide evidence of the co-occurrence of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 105 publications
2
20
0
Order By: Relevance
“…Encoding of the Go‐response, in turn, critically involves auditory‐cortical NMDA receptor signalling (Schicknick & Tischmeyer, ) and was selectively affected in opposite directions when β 1 ‐adrenergic antagonists and agonists were previously applied to naive animals in the present study. Given that catecholamines in the brain in general (Birn et al., ; van den Brink et al., ; Devilbiss, ; Guedj, Meunier, Meunier, & Hadj‐Bouziane, ; Helbing, Tischmeyer, & Angenstein, ) and in the auditory cortex (Happel, ; Happel et al., ; Reichenbach et al., ) shape the functional connectivity of local as well as global circuits, the present findings can be explained by postulating a critical role of β‐adrenergic activity in the auditory cortex for NMDA receptor‐dependent mechanisms of FM discrimination learning that support the strengthening of functional connections required for goal‐directed behaviour.…”
Section: Discussionmentioning
confidence: 61%
“…Encoding of the Go‐response, in turn, critically involves auditory‐cortical NMDA receptor signalling (Schicknick & Tischmeyer, ) and was selectively affected in opposite directions when β 1 ‐adrenergic antagonists and agonists were previously applied to naive animals in the present study. Given that catecholamines in the brain in general (Birn et al., ; van den Brink et al., ; Devilbiss, ; Guedj, Meunier, Meunier, & Hadj‐Bouziane, ; Helbing, Tischmeyer, & Angenstein, ) and in the auditory cortex (Happel, ; Happel et al., ; Reichenbach et al., ) shape the functional connectivity of local as well as global circuits, the present findings can be explained by postulating a critical role of β‐adrenergic activity in the auditory cortex for NMDA receptor‐dependent mechanisms of FM discrimination learning that support the strengthening of functional connections required for goal‐directed behaviour.…”
Section: Discussionmentioning
confidence: 61%
“…A recent study showed that manipulating the NE level in humans modulates the perceptual sensitivity to detect a visual target and this effect reflected changes in evoked potentials and fMRI signals in visual cortex (Gelbard-Sagiv et al 2018). At rest, ATX was also found to reduce the functional correlation strength within sensory networks and to modify the functional connectivity between the LC and the fronto-parietal attention network (Guedj et al 2016(Guedj et al , 2017, involved in visuo-spatial orienting (Corbetta et al 2008) Thus, to get to our second aim that was to characterize the specific action of NE onto the visuo-spatial components, our results points toward two complementary actions of NE, on both bottom-up and top-down processes. Our results bring new evidence to the role of NE on attentional processes.…”
Section: Atx-boosting Effect On Spatial Orienting Reflects Changes Onmentioning
confidence: 98%
“…The effect of neuromodulators on neural activity and connectivity is a critical but often overlooked aspect of brain function. Regional and global release of these molecules can lead to drastic changes in the dynamics and functional connectivity of neural circuits (Bargmann 2012;Bargmann and Marder 2013), and it has often been suggested that neuromodulatory systems may play a key role in triggering and shaping the reconfiguration of functional networks across diverse behavioral states (Guedj, et al 2017a;Hermans, et al 2011;Shine, et al 2019). In line with these theories, alterations of the neuromodulatory neurotransmitters dopamine (Alavash, et al 2018;Shafiei, et al 2018), noradrenaline (Guedj, et al 2017b;Hermans, et al 2011;Shine, et al 2018b;van den Brink, et al 2016), acetylcholine (Klaassens, et al 2017), and serotonin (Klaassens, et al 2017) have all been associated with significant alterations in the architecture and dynamics of BOLD FC networks.…”
Section: Neuromodulatory Influences On Bold Tvcmentioning
confidence: 99%